HUBUNGAN STATUS GIZI DENGAN KEKUATAN DAN KETAHANAN FISIK ATLET BULU TANGKIS - Nimrot manalu; Ahmad Hidayat; Bambang Saputra; Elroygulo; Ferdiansyah Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Badminton is a racket sport that demands complex physical abilities, including muscle strength, aerobic and anaerobic endurance, speed, and agility. This physical performance is greatly influenced by adequate and balanced nutritional intake. This study aims to analyze the relationship between nutritional status and the level of physical strength and endurance in badminton athletes. The method used was an observational study with a cross-sectional approach, involving 30 badminton athletes aged 15–20 years. Nutritional status was measured using Body Mass Index (BMI) and body fat percentage, while physical strength was assessed through grip strength and vertical jump tests, and physical endurance was tested through repeated running tests and core muscle endurance tests. The results showed a positive and significant relationship between good nutritional status and physical strength (p < 0.05), and a very significant relationship with athletes' physical endurance (p < 0.01). Athletes with normal nutritional status had higher average strength and endurance scores than athletes with under or over nutritional status. The conclusion of this study is that nutritional status is one of the main determinants of badminton athletes' physical abilities. Proper nutritional monitoring and management are essential to optimize an athlete's physical potential and performance.